Who Bears the Cost of Russia's Military Draft? - Lokshin, Michael; Yemtsov, Ruslan (2012)
In this paper, we use data from a large nationally representative survey in Russia to empirically estimate the distribution of the burden induced by the military draft. We focus on draft avoidance as a common response to the conscription system ridden by corruption. We develop a simple theoretical model that describes household compliance decisions with respect to enlistment as a function of its pre-draft welfare. We employ the full information maximum-likelihood instrumental variable model to estimate the effect of household characteristics on the probability of serving in the army. Our results indicate that the burden of conscription falls excessively on the poor. Poor, low-educated, rural households are much more likely to have their sons enlisted compared to urban, wealthy and better-educated families. Using the predicted probability of draft avoidance, we estimate the short-term direct economic cost of the draft as lost wages of serving conscripts. Our results suggest that losses incurred by the poor are disproportionately large and exceed the statutory rates of personal income taxes.